Three‐way stopcock suture technique for hemostasis after ablation for atrial fibrillation. (25th September 2018) - Payne, Joshua; Aznaurov, Samuel; Gautam, Sandeep
Abstract: Background: Figure‐of‐eight sutures (F8S) have emerged as an alternative to the standard practice of manual compression to achieve venous hemostasis after catheter ablation for atrial fibrillation (AF). In lieu of a knot to secure the sutures in place, a three‐way stopcock can be used, which can be loosened or tightened as needed to achieve hemostasis and is easier to remove. The safety and effectiveness of this technique, when compared to traditional F8S, are unknown. In this case series, we sought to describe this stopcock closure (SC) technique and compare procedural characteristics and outcomes to the traditional F8S. Methods: Charts of consecutive patients who underwent AF radiofrequency at two centers were reviewed for the type of hemostasis (SC or F8S), demographics, periprocedural anticoagulation, groin complications, and procedural duration. Results: A total of 100 patients were included (50 in the F8S group and 50 in the SC group). The two groups were similar in terms of mean age, gender, weight, renal function, oral anticoagulant use, and procedural heparin dosing. There was one groin bleeding complication in each group. The procedural time was shortened in the SC group (220 ± 8 minutes vs 313 ± 8 minutes), and there was more protamine use (25 vs 3 patients) owing to the differences in preferences among two operators. Conclusion: In this proof‐of‐concept study, a simple stopcock device provided comparable hemostasis to standard F8S after radiofrequency catheter ablation of AF.